PENGARUH INTERAKSI KEPUASAN KERJA DAN WORKPLACE SPIRITUALITY TERHADAP KOMITMEN ORGANISASIONAL (Studi Empiris pada KAP di Semarang) - Sih Mirmaning Damar Endah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Public accounting firm is an independent third party that provide accounting services to help decision making process for the client. All employees in public accounting firm required to have a commitment in their tasks. This research focuses in factors that affecting the organizational commitment. The subject of this research is public accounting firms in Semarang. The aim of this research is to determine the effect of job satisfaction in workplace spirituality to organizational commitment. A case study are the auditors from thirteen Public Accounting Firms in Semarang. In a case study of thirteen Public Accounting Firms, statistical results reveal that job satisfaction significantly influence to organizational commitment with 0,00 significance level. The significance level change to 0,085 and Beta -6,27 when moderated with workplace spirituality. It means workplace spirituality variable debilitated this relationship.Keywords: Organizational Commitment, Workplace Spirituality, Job Satisfaction